2005
DOI: 10.1103/physrevb.72.085304
|View full text |Cite
|
Sign up to set email alerts
|

Interference effects on Kondo-assisted transport through double quantum dots

Abstract: We systematically investigate electron transport through double quantum dots with particular emphasis on interference induced via multiple paths of electron propagation. By means of the slave-boson mean-field approximation, we calculate the conductance, the local density of states, the transmission probability in the Kondo regime at zero temperature. It is clarified how the Kondoassisted transport changes its properties when the system is continuously changed among the serial, parallel and T-shaped double dots… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 62 publications
2
97
1
1
Order By: Relevance
“…Experimentally, it would correspond to spin polarized leads in an infinite magnetic field where only one spin state is accessible by electronic excitations. This spinless DQD model has been used to study the effect of interferences on average currents without [20][21][22] and with [25][26][27]30 an additional Aharonov-Bohm phase.…”
Section: A Model A: Double Quantum Dotmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimentally, it would correspond to spin polarized leads in an infinite magnetic field where only one spin state is accessible by electronic excitations. This spinless DQD model has been used to study the effect of interferences on average currents without [20][21][22] and with [25][26][27]30 an additional Aharonov-Bohm phase.…”
Section: A Model A: Double Quantum Dotmentioning
confidence: 99%
“…17,18 It has been shown that strong Coulomb interactions suppress large current fluctuations. 17 Double quantum dot ͑DQD͒ systems in parallel geometry [19][20][21][22] and single multilevel quantum dots 23,24 can display interference effects due to the multiple paths that electrons take to cross the junction when Coulomb interaction is present. These effects on the average electric current and level population [19][20][21][22][23][24] do not require a magnetic field as in double quantum dot Aharonov-Bohm interferometers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the DQD system in parallel configuration, the physical properties can be quite different, since the interference effect will play an important role in its transport properties. The Fano effect for electron transport through bonding and antibonding channels in DQDs system has been studied [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The Kondo physics has been extensively studied in a wide range of fields from d-or f -electron impurities embedded in bulk materials 2, 3) to artificial atomic systems with metallic lead contacts such as quantum dot (QD) or magnetic molecular devices. [4][5][6][7][8][9] In particular, much attention has been paid to rich Kondo phenomena associated with coupled spin clusters or fabricated quantum devices, for instance, the transport properties between leads through a double 4,6,[10][11][12][13][14][15] or triple QD. [16][17][18][19][20] As a different context, several theoretical studies have recently investigated the Kondo effect for a single impurity in two-dimensional electron gas with the Rashba spin-orbit (SO) coupling.…”
Section: Introductionmentioning
confidence: 99%